2018
DOI: 10.1096/fasebj.2018.32.1_supplement.635.14
|View full text |Cite
|
Sign up to set email alerts
|

An Impact of Images on Multiple‐Choice Questions in Anatomy Examination Score in Nursing Students

Abstract: Anatomy examinations often have a key visual component with the inclusion of many images, and research shows that visualization can have a positive effect on learning (Vorstenbosch et al., 2013) while altering learner's cognitive load, memory and examination anxiety (Mayer RE, 2005). However, most of the studies on the effects of images on anatomy examinations are focused in medical, pre‐nursing, or pre‐health science students but have not yet been assessed in nursing students. To assess the effects of images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In the detailed analysis of the examination scores, we noticed that the mean examination scores of MCQs in online class were relatively higher than the face-to-face class. It is known that correctly solving MCQs requires better understanding of the contents, and this has been acquainted through online teaching methods [25] , [26] . Our findings are consistent with a previous study, which reported that the online learning revealed higher outcomes than the conventional face-to-face methods [27] .…”
Section: Discussionmentioning
confidence: 99%
“…In the detailed analysis of the examination scores, we noticed that the mean examination scores of MCQs in online class were relatively higher than the face-to-face class. It is known that correctly solving MCQs requires better understanding of the contents, and this has been acquainted through online teaching methods [25] , [26] . Our findings are consistent with a previous study, which reported that the online learning revealed higher outcomes than the conventional face-to-face methods [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that nursing students retained 71.0% of their first-year anatomical knowledge in their second year (Narnaware & Neumeier, 2019, 2020b and 51.6% in third-year studies (Narnaware & Neumeier, 2021c). We have initiated many interventional strategies to improve students' long-term retention of anatomical and physiological knowledge, including the use of modern teaching technology (Narnaware & Neumeier, 2021a), content reinforcement (Narnaware & Chahal, 2019), and online and in-class activities (Narnaware et al, 2019). Despite human anatomy being considered a 'visual science' and an imagereliant subject, the impact of images on anatomy exam scores in nursing students has not yet been assessed.…”
Section: Introductionmentioning
confidence: 99%